QUERCETIN AND ELLAGIC ACID IN GASTRIC ULCER PREVENTION: AN INTEGRATED SCHEME OF THE POTENTIAL MECHANISMS OF ACTION FROM IN VIVO STUDY - KOTOB, SOHEIR E; Sayed, Alaa H; Mohamed, Safaa H; Ahmed, Hanaa H (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The present study was initiated to describe the gastroprotective role of quercetin (Qu) and ellagic acid (EA) on aspirin-induced gastric ulcer (GU) in rats. Methods: Forty adult female albino rats of Wistar strain were distributed into: Control group, GU group, Omeprazole group, Qu group, and EA group. Gross examination, biochemical analyses including serum adrenocorticotropic hormone (ACTH), serotonin (ST), ferritin, heme oxygenase-1 (HO-1), interleukin-2 (IL-2), advanced glycosylation end products (AGEs), and fibronectin (FN) levels were estimated. Moreover, histopathological and histochemical examinations of stomach tissue samples were carried out. Results: Gross examination of gastric mucosa of rats in GU group revealed hyperemia of the stomach mucosa. Furthermore, rats in GU group experienced a significant rise in serum ACTH, ferritin, HO-1, IL-2 and AGEs levels accompanied with significant drop in serum ST and FN levels versus control counterparts. Pre-treatment of GU group with Omeprazole, Qu or EA caused marked improvement in the measured biochemical parameters. Histopathological and histochemical examinations of stomach tissue samples documented the protective action of Omeprazole, Qu and EA with different degrees against GU caused by aspirin. Conclusion: As a conclusion to this study, we can state that both Qu and EA have gastroprotective effect against aspirin-induced GU in rat model. Of note, Qu showed superior impact than EA as an antiulcer agent in this study. The corresponding mechanisms are speculated to be associated with inhibiting stress-induced gastric lesion, attenuating the oxidative stress, iron chelation and blunting ferritin level, modulating inflammatory cascade, and promoting the healing process.